Performance Analysis in Palm Oil Industry Using Supply Chain Operations Reference (SCOR) Model - Haryadi Sarjono; Kevin Christofer; Georgie Florensky Nayoan; Mochamad Derisman Nugraha (Binus Business Review, 2022)
The research aims to map the process and measure supply chain performance in the palm oil industry using the Supply Chain Operation Reference (SCOR) Model 11.0 approach. It was considered that this industry could influence the country’s foreign exchange. The object of research was PT Perkebunan Nusantara I (PTPN I), Aceh. It was chosen because, compared to other PTPNs in the Sumatra region, the lowest productivity rate for palm oil processing was around 2,8 tons/ha, inversely proportional to the land area owned by state plantations of 42.233 ha. Data were collected using field survey methods and interviews with company managers involved in the company chain process. This measurement process was useful for measuring achievements and correcting ineffective supply chain processes. The results show that supply chain performance analysis for performance metrics has not reached the expected target. It describes Perfect Order Fulfillment (POF) with a gap of 98%, Order Fulfillment Cycle Time (OFCT) of 3,93 days, Total Cost to Serve (TCTS) of 71%, Cash to Cash Cycle Time (CCCT) of 242,32 days, and Return on Supply Chain Fixed Assets (ROF) of 0,123 times, when viewed from the calculation of the Lost Opportunity Measurement (LOM). In the research, four recommendations for improvement are given based on the problems that occur in the company using the best practices of the SCOR model. They are manufacturing reliability improvement, batch reduction, Single Minutes Exchange of Dies (SMED), and make-to-order fulfillment strategy.